A commercial ELISA for detection of interferon gamma in white rhinoceros. (July 2019) - Chileshe, Josephine; Goosen, Wynand J.; Buss, Peter E.; van Helden, Paul D.; Warren, Robin; Parsons, Sven D. C.; Miller, Michele A.
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is endemic in Kruger National Park, South Africa, home to the largest population of white rhinoceros ( Ceratotherium simum ) in the world. In 2016, the first cases of naturally occurring bTB were reported in white rhinoceros; however, there is a lack of understanding of infection and disease process in this species. Prevention and control of transmission depends on the availability of accurate tools to detect M. bovis infection. Interferon gamma (IFN-γ) assays are a reliable detection method for TB in other animal species, and studies have indicated that these tests can be used in white rhinoceros. We sought to screen and optimize a commercial IFN-γ enzyme-linked immunosorbent assay (ELISA) to detect endogenous white rhinoceros IFN-γ in mitogen-stimulated whole blood as a basis for developing a test for M. bovis infection. Optimizations included identifying ELISA antibodies and determining the effect of sample matrix, ELISA plate incubation temperature, ELISA linearity, assay reproducibility, and the assay's limit of quantification. The optimized assay employed an equine IFN-γ antibody pair that was used to create a commercial ELISA kit. This ELISA had a linear response to recombinant equine and endogenous rhinoceros IFN-γ (range: 7.8–125 pg/mL). When incubated at 37°C, the ELISA was highly reproducible, with an optimal recovery and a low limit of quantification, indicating that the Mabtech equine IFN-γ ELISA PRO kit is a robust assay for measuring white rhinoceros IFN-γ.